Handbook of perceptual dialectology. Volume 1 - Preston, Dennis Richard (Amsterdam ; Philadelphia : J. Benjamins, 1999)
Perceptual dialectology investigates what ordinary people (as opposed to professional linguists) believe about the distribution of language varieties in their own and surrounding speech communities and how they have arrived at and implement those beliefs. It studies the beliefs of the common folk about which dialects exist and, indeed, about what attitudes they have to these varieties. Some of this leads to discussion of what they believe about language in general, or "folk linguistics". Surprising divergences from professional results can be found. For the professional, it is intriguing to f.
HANDBOOK OF PERCEPTUAL DIALECTOLOGY; Title page; LCC page; Dedication; Table of Contents; List of Figures; List of Tables; Preface; Acknowledgments; Introduction; PART I The Dutch Contribution: 'Little Arrows'; CHAPTER 1. Informant Classification of Dialects; CHAPTER 2. Dialects; CHAPTER 3. The Netherlands-German National Border as a Subjective Dialect Boundary; PART II The Japanese Controversy: 'Subjective' and 'Objective'; CHAPTER 4. Consciousness of Dialect Boundaries; CHAPTER 5. Consciousness of Linguistic Boundaries and Actual Linguistic Boundaries.
Includes bibliographical references and index.
Description based upon online resource; title from PDF title page (viewed September 18th, 2023).
English.
eBooks on EBSCOhost
Keywords: Linguistic geography; Speech perception; Language and languages -- Variation; Language awareness; Speech Perception; Géographie linguistique; Perception de la parole; Variation (Linguistique); Conscience linguistique; LANGUAGE ARTS & DISCIPLINES -- Linguistics -- General; Language and languages -- Variation; Language awareness; Linguistic geography; Speech perception; Dialectologie; Spraakwaarneming; Electronic book